THE INFLUENCE OF LEADERSHIP ON THE PROFESSIONAL DEVELOPMENT OF FUTURE MARKETOLOGISTS AND APPROACHES TO ITS IMPLEMENTATION IN HIGHER EDUCATION INSTITUTION - Volkova , Nataliia; Lebid, Olha (Educological discourse, 2022)
The article is devoted to the study of the problem of leadership competence as determinants of professional development of future marketers. It is established that the definition of «leadership» allows for different interpretations, this is due to different views on the nature of the individual, the mechanisms and conditions of its development and formation in different scientific schools. Each theory of leadership theoretically and empirically substantiates some characteristics of the leader, which are manifested in effective professional activity. The views of domestic and foreign scientists on the essence of the concept of «leadership competence» are analyzed. The content of leadership competence of future marketers is defined and revealed. It is noted that leadership competence is a supra-professional competence of the future marketer, which is the key to effective performance of his professional functions by a marketer. The basic competencies that a modern marketing leader should have been clarified. The study takes into account that there is a contradiction between the needs of the labor market in highly qualified leading marketers and the lack of their training in higher education. The Standards of Higher Education Training in the specialty 075 Marketing are analyzed and the general competencies that ensure the formation of leadership competence of future marketers are identified. In order to develop leadership competence, marketers in conditions of uncertainty must become more independent, self-disciplined, manage teams, groups and projects, and therefore have developed leadership skills. Prospects for further research are the development of a system of methods for finding and professional training of effective marketers, followed by improvement and further development of identified leadership qualities.